PENGARUH PENDIDIKAN DAN PELATIHAN, PENGALAMAN ORGANISASI, PEMAHAMAN TENTANG ANGGARAN TERHADAP PERAN ANGGOTA DPRD DALAM PENGAWASAN KEUANGAN DAERAH (STUDI PADA ANGGOTA DPRD KOTA MANADO, KOTA BITUNG DAN PROVINSI SULAWESI UTARA) - Wowor, Reynaldi Dionisius; Manossoh, Hendrik; Wokas, Heince R. N. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
This study aims to examine the influence of education and training, organizational experience, knowledge about budget towards the role of DPRD’s members on financial region supervision. This research is motivated by the facts based on the fact that there is still a weakness in the supervision of regional finances. Dependent variable in this research are the role of DPRD’s members on financial region supervision. Independent variables are education and training, organizational experience,knowledge about budget. The data in this research consist of primary data that taken by the questionnaires which distributed directly to respondents. The data are collected from 60 respondents of DPRD members of Manado City, Bitung City and North Sulawesi Province. The Hipothesis of this study are examine by using the multiple linear regression. The result of this research is indicated that is first, education and training have not  effect towards the role of DPRD’s members on financial region supervision. Second, organizational experience have not effect towards the role of DPRD’s members on financial region supervision. Third, knowledge about budget affect towards the role of DPRD’s members on financial region supervision. The Suggestion for further research is the research instrument of education and training variable, organizational experience variable should be developed.Keywords :   Education and Training, Organizational Experience, Knowledge about Budget, The Role of DPRD Members, Financial Region Supervision